Closing the cultural rights gap in transitional justice: Developments from Canada's National Inquiry into Missing and Murdered Indigenous Women and Girls. Issue 1 (March 2021) - Luoma, Colin
Canada's National Inquiry into Missing and Murdered Indigenous Women and Girls (the 'MMIWG Inquiry') is the latest truth-seeking body to grapple with legacies of violence against indigenous peoples in settler colonial states. While the name, Missing and Murdered, ostensibly limits its scope of application to bodily integrity crimes, the MMIWG Inquiry instead embraced an expansive understanding of violence to encompass gross violations of indigenous cultural rights and cultural harm more generally. This article argues that this holistic approach represents a stark departure from mainstream transitional justice models which have overwhelmingly prioritised the redress of a limited set of civil and political rights violations, while neglecting the underlying structural violence and cultural harm that permeates divided societies. This article advances a case to understand the MMIWG Inquiry as a transitional justice mechanism and draws upon its Final Report to analyse how truth commissions can engage with cultural rights violations in more meaningful ways. By directly and robustly accounting for indigenous cultural harm, the MMIWG Inquiry challenged the conventional parameters of the field and demonstrated the opportunity and utility of addressing cultural rights violations through a transitional justice framework.